Pernikahan disabilitas: Ijab qobul bagi orang yang tunawicara - Safitri, Yuli Kurniawati (Maliki Interdisciplinary Journal, 2023)
Man's life has something very important: marriage. For a man and a woman can be united by a legitimate bond, which is to build an ark of peaceful household, and love for one another. As a sign of a marriage there is a bargain to bind a sacred bond. In Qabul there are many methods in the use of one of them on the part of the spoken or spoken. Can be in Arabic or in the respective regional languages with a record of the sentences pronounced understandable, explicit and deliberately agreed. Except for the bridegroom who has a disability, namely tunawicara or tuna rungu, Imam Ibn Hajr Al-Haitami and Imam Syamsudin Muhammad Ramli said that the bride who suffered from tunawisara or tunarungu in pronouncing ijab | may use or suffice with sign language that is easy to understand and translate.